Maternal Parenting Patterns and Their Association with Stunting Among Children Aged 24–59 Months in Tanah Toa Village, Bulukumba Regency - Syahrir, Sukfitrianty; Syarfaini, Syarfaini; Ibrahim, Irviani; Rajab, Hamdana; Aswadi, Aswadi (Journal of Health and Nutrition Research, 2025)
Stunting remains a persistent problem in Tanah Toa Village, where high rates of growth faltering are closely linked to inadequate maternal parenting practices related to nutrition, hygiene, and health care. This study aimed to analyze the relationship between maternal parenting patterns including feeding practices, psychosocial stimulation, hygiene practices, environmental sanitation, and health service utilization and stunting among children aged 24–59 months in Tanah Toa Village, Bulukumba Regency. This cross-sectional study involved 111 mother–child pairs, with data collected from October to November 2020 using structured questionnaires and anthropometric measurements. Data were analyzed using the Chi-square test and binary logistic regression using SPSS version 26.0. The results showed significant associations between stunting and hygiene practices (p = 0.003), environmental sanitation (p = 0.000), health service utilization (p = 0.049), and overall maternal parenting patterns (p = 0.000). Multivariate analysis identified maternal parenting patterns as the most dominant factor influencing stunting (p = 0.010; OR = 0.124; 95% CI = 0.03 to 0.62). Children raised by mothers with good parenting practices were 0.124 times less likely to experience stunting compared to those raised by mothers with poor parenting. These findings highlight that comprehensive parenting which involves nutrition, hygiene, and health care plays a critical role in preventing stunting. Interventions should integrate nutrition education, maernal empowerment, and culturally grounded health promotion to accelerate stunting reduction at the community level.